Colorimetric Sensing of Hg2+ and Fe3+ Ions in aqueous solution using Green Synthesized Silver Nanoparticles: Life Sciences-Chemistry for better environment - Pinaki Mandal; Samir Maji (International Journal of Life Science and Pharma Research, 2022)
Plant extracts have a very important role for the synthesis of different nanoparticles due to its reducing capability, availability and nontoxicity. Biosynthesized silver nanoparticles were investigated for colorimetric sensing of metal ions at different concentrations. Aqueous leaf extract of Plumeria alba was used as bio reduction to synthesize stable Silver nanoparticles (AgNPs). A possible interaction between AgNPs and metal ions at different concentrations was proposed on the basis of UV-Vis spectral analysis. The produced silver nanoparticles were characterised by different technique which includes UV–vis spectroscopy and transmission electron microscopy (TEM). The intensity of the localized surface plasmon absorption band at 438 nm in UV-visible spectrum confirmed the presence of silver nanoparticles. TEM analysis showed the spherical and irregular particles shape and size of nanoparticles ranging from 20 to 100 nm. Metal ion sensing properties of these AgNPs in aqueous solution has been explored. In the detection of different metal ions using these green synthesized AgNPs, the promising colorimetric response was observed with naked eyes and spectroscopic changes were examined by using a UV-Visible spectrophotometer. The colorimetric sensor studies showed selective sensing of Fe3+ and potentially hazardous Hg2+ ions in aqueous medium with a limit of detection of about 0.2 mM concentrations. This method may be applied as low cost and high potential colorimetric sensor for the selective recognition and monitoring of Hg2+ and Fe3+ ions in biological, pharmaceutical samples as well as in water.